Frontiers in Bioenergy and Biofuels 2017
DOI: 10.5772/66189
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Proteomics as a Means to Identify Target Genes to Improve Second‐Generation Biofuel Production

Abstract: Second-generation biofuels "2G generally uses residues composed of lignocellulosic materials to produce renewable energy potentially up to 50% , without increasing the planted areas. However, the high cost of enzymes required for cell wall disassembly prior to the sacchariication makes the "2G production more expensive yet, compared to the irst-generation biofuels. Designing plants with less lignin, a barrier to "2G production, or facilitating cell wall disassembly by searching for the plant mechanisms can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…The importance of GHs in different physiological processes such as root aerenchyma formation ( Grandis et al, 2019 ), proper cell wall deposition ( Moneo-Sánchez et al, 2019 , 2020 ), and xylem differentiation ( Yu et al, 2013 ; Hu et al, 2020 ; Tu et al, 2020 ) was shown. Despite a wide variety of GHs acting during different processes has been described in several omics studies ( Francin-Allami et al, 2015 ; Calderan-Rodrigues et al, 2017 ; Grandis et al, 2019 ), in many cases, the physiological significance of these GHs in plants has remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of GHs in different physiological processes such as root aerenchyma formation ( Grandis et al, 2019 ), proper cell wall deposition ( Moneo-Sánchez et al, 2019 , 2020 ), and xylem differentiation ( Yu et al, 2013 ; Hu et al, 2020 ; Tu et al, 2020 ) was shown. Despite a wide variety of GHs acting during different processes has been described in several omics studies ( Francin-Allami et al, 2015 ; Calderan-Rodrigues et al, 2017 ; Grandis et al, 2019 ), in many cases, the physiological significance of these GHs in plants has remained elusive.…”
Section: Introductionmentioning
confidence: 99%